Cycle rate variations in roller ski skating: effects on oxygen uptake and poling forces - Millet, G. Y.; Hoffman, M. D.; Candau, R. B.; Buckwalter, J. B.; Clifford, P. S. (International Journal of Sports Medicine, 1998)
The purpose of this study was to examine the effect of cycle rate (CR) variations on the metabolic cost and upper body forces during roller skiing with the V2-alternate technique on flat terrain. Nine highly skilled cross-country skiers roller skied at a paced speed of 18.0+/-0.1 km x h(-1) using their chosen CR, and CRs that were 10% slower and 20% faster. Oxygen uptake (VO2) was determined through collection of expired gases into a meterological balloon and poling forces were measured with piezoelectric transducers during the last 30 s of each four minute trial of roller skiing. One-way repeated measures ANOVA revealed that VO2 varied significantly with CR (p=0.02) with the chosen CR being significantly lower than the higher CR (p < 0.05). Poling forces and poling time were not significantly different among the CR conditions. The present results demonstrate that 1) an alteration in cycle rate affects metabolic cost of roller ski skating, 2) skiers tend to naturally select the most economical cycle rate, and 3) moderate variations in cycle rate do not appear to affect propulsive force generation through the poles in roller skiing.